Analyzing the scope of Refinancing schemes using scenario and gender disparity analysis within pre and post Covid Bangladesh - Fairuz, Aliya (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.